Influence of traditional processing and genotypes on the antioxidant and antihyperglycaemic activities of yellow-fleshed cassava - Kareem, Babajide; Irondi, Emmanuel Anyachukwu; Alamu, Emmanuel Oladeji; Ajani, Emmanuel Oladipo; Abass, Adebayo; Adesokan, Michael; Parkes, Elizabeth; Maziya-Dixon, Busie (Frontiers in Nutrition, 2022)
Yellow-fleshed cassava root (YFCR), an important dietary source of β-Carotene, is processed into traditional products that may influence its bioactivities. In this study, the antioxidant, starch-digesting enzymes inhibitory properties, and glycaemic index (GI) of three traditional products (lafun, fufu and gari) from five genotypes (IITA-TMS-IBA070337, 182961, 182962, 182986, 183044) of YFCR were evaluated. The YFCR genotypes were grown at the International Institute of Tropical Agriculture (IITA) research field, Ibadan. The bioactive constituents (total carotenoids, total phenolics, tannins and total flavonoids), antioxidant [2,2-azinobis (3-ethyl-benzothiazoline-6-sulfonic acid) radical cation (ABTS*+) and 1,1-diphenyl-2- picrylhydrazyl radical (DPPH*) scavenging capacities, and reducing power), and starch-digesting enzymes (α-amylase and α-glucosidase) inhibitory activities of the products were determined using standard laboratory methods. The GI of the products was assessed in human subjects. The concentrations of the bioactive constituents of the products from different genotypes varied significantly (p < 0.05). The ABTS*+ and DPPH* scavenging capacities and the reducing power of the products also differed significantly (p < 0.05), such that the lafun from IITA-TMS-IBA182962, IITA-TMS-IBA070337 and IITA-TMS-IBA070337 had the strongest ABTS*+ and DPPH* scavenging capacities, and reducing power, respectively. The α-amylase and α-glucosidase inhibitory activities of the three products differed significantly (p < 0.05), with the lafun from IITA-TMS-IBA070337 and IITA-TMS-IBA07033 having the strongest α-amylase and α-glucosidase inhibitory activity, respectively. Also, the lafun from IITA-TMS-182986 had the least GI, while the fufu from IITA-TMS-IBA070337 had the highest GI. Overall, the lafun from different genotypes of YFCR had the most potent antioxidant and starch-digesting enzymes inhibitory activities and the least GI. Hence, lafun may be a promising dietary intervention targeting oxidative stress, hyperglycaemia, and their resultant type 2 diabetes.